The relation between bisphosphonate use and non-union of fractures of the humerus in older adults - Solomon, D. H. (2008)
SUMMARY: While nitrogen-containing bisphosphonates have been shown to reduce fracture risk in postmenopausal women and men, their safety in the period after a fracture is unclear. In fully adjusted multivariable regression models, bisphosphonate use in the post-fracture period was associated with an increased probability of non-union [odds ratio (OR) 2.37, 95% confidence interval (CI) 1.13–4.96]. Clinicians might consider waiting for several months before introduction of a bisphosphonate after a fracture. INTRODUCTION: While nitrogen-containing bisphosphonates have been shown to reduce fracture risk in postmenopausal women and men, their safety in the period after a fracture is unclear. We examined the risk of non-union associated with post-fracture bisphosphonate use among a group of older adults who had experienced a humerus fracture. METHODS: We conducted a nested case–control study among subjects who had experienced a humerus fracture. From this cohort, cases of non-union were defined as those with an orthopedic procedure related to non-union 91–365 days after the initial humerus fracture. Bisphosphonate exposure was assessed during the 365 days prior to the non-union among cases or the matched date for controls. Multivariable logistic regression models were examined to calculate the OR and 95% CI for the association of post-fracture bisphosphonate use with non-union. RESULTS: From the cohort of 19,731 patients with humerus fractures, 81 (0.4%) experienced a non-union. Among the 81 cases, 13 (16.0%) were exposed to bisphosphonates post-fracture, while 69 of the 810 controls (8.5%) were exposed in the post-fracture interval. In fully adjusted multivariable regression models, bisphosphonate use in the post-fracture period was associated with an increased odds of non-union (OR 2.37, 95% CI 1.13–4.96). Albeit limited by small sample sizes, the increased risk associated with bisphosphonate use persisted in the subgroup of patients without a history of osteoporosis or prior fractures (OR 1.91, 95% CI 0.75–4.83). CONCLUSIONS: In this study of older adults, non-union after a humerus fracture was rare. Bisphosphonate use after the fracture was associated with an approximate doubling of the risk of non-union.